High gain boost converter with modified voltage multiplier for stand alone PV system - Getzial Anbu Mani; A. K. Parvathy (Institute of Advanced Engineering and Science, 2019)
Boost converters of high gain are used for photo voltaic systems to obtain high efficiency. These high gain Boost converters gives increased output voltage for a low input produces high outputs for low input voltage. The High gain boost converters have the following merits. Conduction losses input current ripple and stress across the switches is reduced while the efficiency is increases. The high gain of the converters with the above said merits is obtained by changing the duty cycle of switches accordingly .In this paper a boost converter working with interleaved concept along with a additional Nstage voltage Multiplier has been carried out by simulation using MATLAB/ simulink and the mathematical modeling of various parameters is also done.